Reportage on the Marcoses, 1964-1970 - Joaquin, Nick 1917- (2013)
Essays on the lives of Imelda and former President Ferdinand Marcos covering his political career, their courtship from 1964 to 1970.
Gift and Donation
Keywords: Marcos, Ferdinand E. -- 1917-1989.; Marcos, Imelda Romualdez -- 1929-.; Philippines -- Politics and government -- 1946-.